Anthropometric measurement for disable students / Nur Amanina Zainal - Nur Amanina , Zainal (2017)
The aim of this study is to collect an anthropometric data of disabled students in Special Education School and Integrated Special Education Program at selected primary schools in area of Kuala Lumpur and Selangor. Fifty two students at mean age of 10 and 9 and standard deviation of 2 for male and female students with hearing disability, vision disability and learning disorder disability are involved in this study. Anthropometric data of selected body dimension which are stature, sitting height, sitting popliteal height, sitting shoulder height, sitting arm height, hips breadth and shoulder breadth are measured and recorded. Current furniture dimensions such as seat height, seat width, backrest height, and arm rest height, desk height and desk width are recorded as well. Current furniture measurement collected are compared with selected body dimensions to identify whether it is suitable for the children. Analysis of the data between current furniture measurement and anthropometric data found that particular dimension of the furniture does not suitable with the anthropometric measured from survey. Therefore, recommended dimension for suitable furniture measured is proposed.